Implementation of Smart Communication BOT Model Using Machine Learning with the N-Gram Method - Irfan Santiko; Muhammad Arifin (Journal of Multimedia Trend and Technology, 2023)
The world of higher education in providing educational services, makes a lot of effort made by the service department at each institution. These efforts are often encountered in certain moments such as before the acceptance of new students. But how is time other than that moment used? Certainly this is related to how to make a strategy so that the market share of these educational institutions is wider. Service and handling is a priority for a company engaged in the world of services. With the ability to develop information technology, it will be able to provide support for service methods and handling to customers. The point is to make service and handling more optimal compared to the usual method. Cannot be separated from the rules, policies, processes and procedures that are owned by every service company. Systematically the technology that will be used also follows the outline of the rules, policies and procedures previously mentioned. This research will be conducted at higher education institutions where an institution is engaged in educational services. This data processing uses machine learning with the N-Gram method. This system will run on the front office or customer service side. The purpose of the results of this research is to be more useful and to assist customer service in higher education institutions in providing services to prospective students or student guardians.